Optimasi Produksi Bioetanol dari Limbah Kulit Pisang Melalui Variasi Waktu Fermentasi Menggunakan Saccharomyces Cerevisiae - Lahagu, Analisi; Zai, Mitra Semestriani; Lawolo, Riniat; Gulo, Piderman; Waruwu, Yuri; Zega, Novelina Andriani (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effect of fermentation duration on the bioethanol yield and to determine the optimal fermentation time using Saccharomyces cerevisiae yeast. The research method involved several main stages: preparation of banana peel samples, acid hydrolysis (using H₂SO₄) to convert polysaccharides into glucose, and anaerobic fermentation. The fermentation times used in this study were 3, 5, 7, and 9 days with a constant concentration of Saccharomyces cerevisiae inoculum. The bioethanol content was measured using a distillation method followed by alcohol content measurement using an alcohol meter or gas chromatography (GC). The results showed that fermentation time had a significant effect on the bioethanol yield. The bioethanol content increased until it reached an optimal point on the 5th day (or adjust according to your data) with a content of ...%, and tended to decrease at longer fermentation times due to the depletion of nutrients in the medium and the accumulation of by-products that inhibited yeast growth. Based on these results, it can be concluded that banana peel waste is effective for use as a bioethanol substrate with an optimal fermentation time of 5 days.